The Nigerian Navy, 1956-1966: Manpower And Platform Development And The First Court Martial - William Abiodun Duyile (Britain International for Academic Research (BIAR-Publisher), 2024)
This paper examined the establishment of the Nigerian Navy and the circumstances surrounding its origin. It narrated the conditions that led to the first naval court martial, examining if there was any ethno coloration in the event. The research also studied the sources, as well as the nature of its early development within the first ten years of its existence. The research in addition analyzed the impact of the British or colonial government on the creation of the Nigerian Navy. The study relied heavily on documentary data and lightly on oral data. The oral data were based on unstructured interviews with few former senior naval officers; and the documentary data were sourced from colonial government annual departmental reports, correspondence, books and magazines. The oral data were transcribed for analysis. The documentary data were subjected to textual and contextual analysis. The researcher found out that the emergence of the Nigerian Navy was the result of interplay of forces such as the ex Royal naval officers, Nigerian nationalists and the colonial administrators. It examined the first court martial.